The devouring - Benn, James R. (A Billy Boyle WWII mystery, 2017)
"A murder in wartime Switzerland reveals Swiss complicity with the Nazis and profiteering during World War II. Billy and Kaz are sent to neutral Switzerland to investigate the murder of a Swiss banking official with ties to the Office of Strategic Services (OSS). The US and Swiss governments are about to embark on diplomatic discussions regarding the Safehaven Protocols, which are aimed at limiting the amount of war materials exported by Switzerland to the Nazis, halting the laundering of looted gold, and preventing the postwar use of Nazi wealth for war criminals. With the talks about to begin, the OSS wants their involvement in the murder cleared up, as well as to protect the participants from any threat of violence. The plans go wrong from the beginning when Billy and Kaz crash-land in France. As they make their way through occupied territory to the border, they meet Anton Lasho, a member of the Sinti ethnic group, whose family was slaughtered by the Nazis, and who is, in turn, a one-man Nazi-killing machine. They'll need his help, because as they find once they make it across the border, Swiss banks are openly laundering gold 'harvested' from concentration camps, and those that are profiting will do everything they can to protect their wealth and hide their dark secrets"--